1990
DOI: 10.1021/bi00458a031
|View full text |Cite
|
Sign up to set email alerts
|

Environments and conformations of tryptophan side chains of gramicidin A in phospholipid bilayers studied by Raman spectroscopy

Abstract: Raman spectroscopy has been used to investigate the hydrophobic interaction of the indole ring with the environments, the water accessibility to the N1H site, and the conformation about the C beta-C3 bond for the four tryptophan side chains of gramicidin A incorporated into phospholipid bilayers. Most of the tryptophan side chains of the head-to-head helical dimer transmembrane channel are strongly interacting with the lipid hydrocarbon chains, and the hydrophobic interactions for the rest increase with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 54 publications
10
47
0
Order By: Relevance
“…Indole orientations determined for the Trp side chains are consistent with Raman scattering (18) which requires 2 to be approximately Ϯ90°. Furthermore, it has been shown that the extent of lipid ; however, all four Trp residues interact with the hydrophobic acyl chains of the lipid (19). The DSDH dimer conformation is fully consistent with these observations having Trp 15 exposed to water near the top and bottom of the dimer and Trp 9 exposed only to lipid.…”
Section: The Dsdh Conformation In Lipid Membranessupporting
confidence: 74%
“…Indole orientations determined for the Trp side chains are consistent with Raman scattering (18) which requires 2 to be approximately Ϯ90°. Furthermore, it has been shown that the extent of lipid ; however, all four Trp residues interact with the hydrophobic acyl chains of the lipid (19). The DSDH dimer conformation is fully consistent with these observations having Trp 15 exposed to water near the top and bottom of the dimer and Trp 9 exposed only to lipid.…”
Section: The Dsdh Conformation In Lipid Membranessupporting
confidence: 74%
“…As indicated by the significant contribution from the electrostatic interaction, the tryptophan side chains are capable of forming hydrogen bonds with the ester carbonyl groups ofthe lipids and the water, whereas the leucine side chains are not. The existence of these hydrogen bonds for the tryptophans are consistent with 2H exchange and IR studies (27,28). For both leucine and tryptophan side chains, the alkane chains are energetically the strongest interacting component.…”
supporting
confidence: 80%
“…In the case of the Trp-Trp dipeptide the negative ellipticity in the near-UV region was attributed to a restriction of the side-chain torsional angles xi and X2 although one might expect their actual values and not just their variability to be important. Raman spectroscopy has indicated a narrow range of Trp X2 angles in the channel form of gramicidin [12]. This corroborates energy calculations which have indicated large barriers for side chain rotation [13].…”
Section: Peptide and Prolein Conformationsupporting
confidence: 83%